Literature Review: Determinan Risiko Fisik terhadap Keluhan Musculoskeletal Disorders pada Pekerja Industri - Risnanda Syauqiyah; Yuanita Windusari; Novrikasari Novrikasari (Jurnal Ragam Pengabdian, 2026)
Musculoskeletal Disorders (MSDs) are a major occupational health problem experienced by industrial workers globally. WHO (2023) reported that approximately 1.71 billion people are affected by MSDs, contributing to 17% of Years Lived with Disability (YLDs). In Indonesia, the prevalence of MSDs among industrial workers reaches 24.7%. This study aims to analyze the physical risk determinants associated with MSDs complaints through a systematic literature review. The method used is a systematic literature review with a thematic descriptive approach through Google Scholar, ScienceDirect, PubMed, and DOAJ databases for the 2021–2025 period, yielding 8 relevant articles. Thematic analysis grouped physical risk factors including work posture, manual handling, repetitive movements, static work duration, and working environment conditions. The review findings indicate that physical risk factors have a significant relationship with MSDs, with non-ergonomic work posture being the most consistent factor, particularly in the neck and shoulder areas. Manual handling increases biomechanical stress on the lumbar spine, while repetitive movements cause progressive muscle fatigue. These findings are consistent across industrial sectors such as electronics, textiles, metal, and construction. MSDs prevention should be carried out through work posture improvement, use of ergonomic tools, task rotation, and scheduled rest breaks to reduce prevalence and improve worker productivity sustainably.